2013
DOI: 10.1186/1472-6882-13-212
|View full text |Cite
|
Sign up to set email alerts
|

Moringa Oleifera aqueous leaf extract down-regulates nuclear factor-kappaB and increases cytotoxic effect of chemotherapy in pancreatic cancer cells

Abstract: BackgroundFewer than 6% patients with adenocarcinoma of the pancreas live up to five years after diagnosis. Chemotherapy is currently the standard treatment, however, these tumors often develop drug resistance over time. Agents for increasing the cytotoxic effects of chemotherapy or reducing the cancer cells’ chemo-resistance to the drugs are required to improve treatment outcome. Nuclear factor kappa B (NF-kB), a pro-inflammatory transcription factor, reportedly plays a significant role in the resistance of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
136
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(144 citation statements)
references
References 19 publications
(26 reference statements)
2
136
0
6
Order By: Relevance
“…oleifera has many medicinal values as research had shown that it possesses antimicrobial, anti-inflammatory, hepatoprotective, antiulcer, antidiuretic activities [38-41] and more importantly to this review, preclinical studies proved it has growth inhibitory effect to proliferation of many cancer types [4][5][6]. For example, Charoensin [42] carried out a two-stage successive extraction of phytochemicals of M. oleifera leaf using methanol, and dichloromethane solvents.…”
Section: Moringa Oleifera Is a "Wonderful Tree"mentioning
confidence: 99%
See 1 more Smart Citation
“…oleifera has many medicinal values as research had shown that it possesses antimicrobial, anti-inflammatory, hepatoprotective, antiulcer, antidiuretic activities [38-41] and more importantly to this review, preclinical studies proved it has growth inhibitory effect to proliferation of many cancer types [4][5][6]. For example, Charoensin [42] carried out a two-stage successive extraction of phytochemicals of M. oleifera leaf using methanol, and dichloromethane solvents.…”
Section: Moringa Oleifera Is a "Wonderful Tree"mentioning
confidence: 99%
“…It has value in tumour therapy and has been found to have the potential of preventing cancer [3]. Aqueous and solvent extracts of M. oleifera leaves have been reported to have significant antiproliferative effects on colon, alveolar, and pancreatic cancer cells and induce apoptosis in KB cells and other cancer cells [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The leaves of Moringa contains some bioactive compounds called β -sitosterol which are highly involved in the effects on the cancer inducing tumour cells [10], which can also shows increased cytotoxicity on pancreatic cancer cells [11]. The antioxidant property of Moringa may be due to the presence of phenolic compounds present in the different parts of the tree.…”
Section: Introductionmentioning
confidence: 99%
“…rubra and Tinospora crispa (TiC). These extracts have previously demonstrated anti-proliferative effects via modulation of the apoptotic pathways (6)(7)(8)(9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…MOs and M. oleifera leaf extracts have been observed to induce CCA cell apoptosis by inducing reactive oxygen species accumulation and mitochondrial dysfunction (8). M. oleifera leaf extract inhibits pancreatic cancer cells by targeting the NF-κB signaling pathway, increasing the efficacy of chemotherapeutic agents in human pancreatic cancer cells (9). Cucurbitae-type triterpene glycosides from M. charantia fruit (MCf) inhibit NF-κB and activate PPAR in HepG2 cells (10).…”
Section: Introductionmentioning
confidence: 99%